PENGARUH KEPEMIMPINAN KARISMATIK KIYAI DAN BUDAYA ORGANISASI DALAM PEMBENTUKAN KARAKTER SANTRI DI PONDOK PESANTREN AL-AMIN PARENDUAN KABUPATEN SUMENEP - Rohim, Robi; Wildan, Muhammad Alkirom (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The aim of the research is to determine the factors that can influence the character of students. The population in this study was 8,086 students at the Al-Amien Perenduen Islamic Boarding School, Sumenep Regency. The sampling technique used was simple random sampling, so that a sample of 100 students was obtained. This research is quantitative research using the variabels kiyai leadership style (X1) and organizational culture (X2) as independen variabels. Meanwhile, the student character variabel (Y) is the dependent variabel. This research uses primary data by distributing questionnaires to respondents. The primary data obtained was then analyzed using SPSS. The data analysis techniques used include data quality testing, classical assumption testing and hypothesis testing using multiple linear regression analysis. The results of the research show that the kiyai's leadership style and organizational culture on the character of the students at the Al-Amien Perenduen Islamic Boarding School, Sumenep Regency, have a very strong or very high correlation. The kiyai's leadership style and organizational culture have an influence of 65.61% on the character formation of students at the Al-Amien Perenduen Islamic Boarding School, Sumenep Regency.